간호대학생의 다문화 인식과 문화적 역량이 다문화 수용성에 미치는 영향 - 조영미(Young Mi Cho); 석소현(So Hyune Sok) (한국콘텐츠학회 논문지, 19(10), 2019)
Purpose: The purpose of this study was to investigate the correlation and the degree of multicultural perception, cultural competence, and multicultural acceptance of nursing college students. METHODS: The study was analyzed using the SPSS 25.0 program. The correlation among multicultural perception, cultural competence, and multicultural acceptance was analyzed by Pearson's correlation coefficients, and it was analyzed using Multiple Regression to figure out factors influencing multicultural acceptance. RESULTS: Multicultural acceptance was a significant positive correlation with multicultural perception and cultural competence of nursing college students (r = .645, p <.001; r = .556, p <.001). As a result of regression analysis, it was confirmed that multicultural perception (${β}=0.479$, p <.001) and cultural competence (${β}=0.299$, p <.001) were factors that influence nursing students' multicultural acceptance. Conclusion: Based on the results of this study, it is suggested that nursing students should develop cultural competency as a way to increase multicultural acceptance in a multicultural society. Also, in developing and implementing multicultural education programs, it is necessary to develop multicultural education program content and the policy backing should be supported that promotes multicultural perception and enhances cultural competence. 목적: 본 연구의 목적은 간호대학생의 다문화 인식, 문화적 역량, 그리고 다문화 수용성의 정도와 상관관계를 알아보고, 다문화 수용성에 영향을 미치는 요인을 파악하기 위해 실시되었다. 방법: 본 연구는 SPSS 25.0 프로그램을 통해 분석하였다. 다문화 인식, 문화적 역량, 다문화 수용성의 상관관계는 Pearson's correlation coefficients로, 다문화 수용성에 영향요인인 다중회귀분석(Multiple Regression)을 사용하여 분석하였다. 결과: 간호대학생들의 다문화 수용성은 다문화 인식과 문화적 역량에 유의한 양의 상관관계(r=.645, p<.001; r=.556, p<.001)가 있었고, 회귀분석 결과 간호대학생의 다문화 수용성에 영향을 미치는 요인은 다문화 인식(${β}=0.479$, p<.001)과 문화적 역량(${β}=0.299$, p<.001)임을 확인하였다 결론: 본 연구결과를 토대로 간호대학생들은 다문화 사회에서 다문화 수용성을 높이기 위한 방안으로 문화적 역량을 키워야 함을 시사한다. 또한 다문화교육 프로그램의 개발 및 시행, 그 내용을 구성하는데 있어 다문화 인식의 고취와 문화적 역량을 높이는 콘텐츠를 개발하고 정책적인 뒷받침이 있어야 할 것이다.